Blood glucose and erythrocyte glutathione level in malnourished children - Saraçlar, Yıldız; Özsoylu, Şinasi (The Turkish Journal of Pediatrics, 1965)
In 27 children with severe malnutrition, blood sugar levels were found to be within normal limits for this age group. Their red cell GSH levels and GSH stability tests were normal. Low erythrocyte GSH values and GSH instability were demonstrated in a G6PD deficient control group as would be expected.